2005
DOI: 10.1002/pmic.200401108
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics profiling of nuclear proteins for kidney fibroblasts suggests hypoxia, meiosis, and cancer may meet in the nucleus

Abstract: Proteomics methods were used to characterize proteins that change their form or abundance in the nucleus of NRK49F rat kidney fibroblasts during prolonged hypoxia (1% O(2), 12 h). Of the 791 proteins that were monitored, about 20% showed detectable changes. The 51 most abundant proteins were identified by mass spectrometry. Changes in nuclear receptor transcription factors (THRalpha1, RORalpha4, HNF4alpha, NUR77), other transcription factors (GATA1, AP-2alpha, OCT1, ATF6alpha, ZFP161, ZNF354A, PDCD2), and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 167 publications
4
35
0
1
Order By: Relevance
“…Similarly, D'Mello and Galli (33) reported that Rp8 mRNA was not induced in neuronal apoptosis triggered in a culture system by nerve growth factor deprivation. Recently, proteomic methodology was used to study proteins in rat kidney fibroblasts during prolonged hypoxia (34). In this study, Rp8 levels were found to increase at least 2-fold in cells subjected to 1% oxygen for a 12-h period.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, D'Mello and Galli (33) reported that Rp8 mRNA was not induced in neuronal apoptosis triggered in a culture system by nerve growth factor deprivation. Recently, proteomic methodology was used to study proteins in rat kidney fibroblasts during prolonged hypoxia (34). In this study, Rp8 levels were found to increase at least 2-fold in cells subjected to 1% oxygen for a 12-h period.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore hypoxia causes dynamic changes in protein subcellular location involving functions that go far beyond changes in glycolysis and include TCA-cycle, OxPhos and chromatin remodeling proteins among many others. 42,71 Several years ago we demonstrated that numerous glycolytic enzymes translocate to the nucleus under hypoxia 71 -the present results suggest that similar dynamic subcellular distributions may be operative for other functional systems such as oxidative phosphorylation and the TCA-cycle and may contribute to cancer and other diseases.…”
Section: Potential Connections To Cancermentioning
confidence: 97%
“…GAPDH, PGAM1, PKM2 and LADH were changed by hypoxia. 71 In recent years participation of ENO1, FBP1, GAPDH, PKM2 and LADH in transcription in the nucleus has been demonstrated by others (Supporting Information Table 5). Very recently, connections to the cell cycle have been established for nuclear FBP1 72 and PGAM1 in the nucleus of cancer cells has been observed.…”
Section: Proteins Involved In Glycolysismentioning
confidence: 99%
“…SYCP2 is part of the synaptonemal complex involved in forming lateral elements and cross bridges that contribute to pairing of sister chromatids during meiosis and probably are involved in the interaction between chromatin and nuclear envelope. 59 There is evidence that HPV infection in cervical cells promotes morphological changes in the nuclear membrane as well as condensation of chromatin attached to the inner part of the nuclear membrane. 60 Thus, it is possible that SYCP2 may be involved in chromatin-nuclear envelope interactions in HPV-positive SCCHN.…”
Section: Discussionmentioning
confidence: 99%